Beyond plastisphere transfer, deep corals are subject to dysbiosis when exposed to plastics - Chapron, L.; Meistertzheim, A.-L.; Ghiglione, J.-F.; Peru, E.; Galand, P.E.; Lartaud, F. (Environmental pollution (1987), 2025)
Plastic pollution has been identified as a major threat to marine life and ecosystems, but their biological impacts are still largely unknown. Coral reefs, which are one of the most biodiverse ecosystems on earth that provide essential ecological and economical services, are now recognized to be impacted by plastic pollution from the surface to the deep. Here, we investigated the impact of colonized macro- and microplastics on the microbiome of the most emblematic cold-water coral, Lophelia pertusa. Studies at the associated bacterial level help better understand the early biological pathways that may lead to coral physiological alterations. Both macro- and microplastics induced early (7 days) microbial shifts for L. pertusa polyps, with specific exacerbated effects between plastic sizes observed after 47 days. In the case of stressed corals, we observed an increase of opportunistic and/or pathogenic bacteria that may be induced by different processes whether corals are exposed to macro- (barrier effect) or microplastics (ingestion). Our results however confirm that very few specific bacteria can be directly transferred from plastisphere to coral microbiome. We suggest that shift in coral microbiome was due to general dysbiosis from stress, and poorly from a transfer of microorganisms from the plastisphere. Considering the widespray distribution of macroplastics in the ocean that are continuously fragmented into microplastics, our conclusions suggest that plastics could seriously endangered the cold-water coral reefs. [Display omitted] •Both macro- and microplastics induced microbial changes for Lophelia pertusa microbiome.•The Microbial shift differ between macroplastics and microplastics.•Increase in opportunistic and/or pathogenic bacteria was observed for stressed L. pertusa.•The observed dysbiosis was due to stress, and poorly to bacterial transfer from the plastisphere.